Alternative pathways to diversity across ecologically distinct lizard radiations. Issue 3 (16th December 2019) - Skeels, Alexander; Esquerré, Damien; Cardillo, Marcel
Abstract: Aim: Lizard assemblages vary greatly in taxonomic, ecological and phenotypic diversity, yet the mechanisms that generate and maintain these patterns at a macroecological scale are not well understood. We aimed to characterize the ecological and environmental drivers of species richness patterns in the context of macroecological theory for 10 independent lizard radiations. Location: Global. Time period: Present day. Major taxa: Lizards. Methods: We analysed patterns of species and functional trait diversity in 10 ecologically distinct and widely distributed clades encompassing nearly all known lizard species. Using recently published spatial, phylogenetic, and functional trait datasets, we built spatially explicit structural equation models to ask whether species richness was directly or indirectly related to functional divergence or convergence within communities, and with features of the environment, including measures of productivity, complexity and harshness. Results: Our results show that high species richness is achieved via different pathways in different lizard clades, with both functionally divergent and convergent assemblages harbouring high diversity in different clades. More generally, we also find common, positive effects of temperature, productivity and topography on species richness within lizard clades. Main conclusions: Thermal constraints, topographic complexity and spatial structuring of functional diversity help explain the presence of highly diverse lizard assemblages, suggesting the importance of environmental filters in shaping present‐day diversity and assemblage structure. Our results show how different pathways to high richness in different clades have contributed to the overall global pattern of species richness in reptiles.